STRATEGY TO IMPROVE CURRENT ACCOUNT PT BANK CENTRAL ASIA TBK KCU MEDAN - Sulastri; Evawany Yunita Aritonang; Fahmi Natigor Nasution (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Current Account is an important indicator in the banking industry because it offers a stable source of cheap funds for banks, which will increase the profitability of the Bank. Current Account in banks is a checking account. This study aims to determine and examine customer perceptions of Current Account services and products offered by PT Bank Central Asia Tbk KCU Medan, to determine and examine the factors that influence the increase in the number of checking accounts (Current Account) at PT Bank Central Asia Tbk KCU Medan and to determine and examine the marketing strategy implemented by PT Bank Central Asia Tbk KCU Medan in increasing the number of Current Account customers. The type of research used is qualitative research combining two analysis techniques, namely SWOT analysis with Systematic Literature Review or called (SLR). Data collection is in the form of observation, interviews and documentation. The informants in this study numbered 12 people. Data analysis is applied through SWOT, Space Matrix and QSPM analysis. The results of the study indicate that the marketing strategy implemented by PT Bank Central Asia Tbk KCU Medan in increasing the number of current account customers is carried out using SWOT analysis to determine strengths, weaknesses, opportunities and threats. So that 20 alternative strategies were found that can be implemented through 5 (five) SO (Strengths-Opportunities) Strategies, 5 (five) WO (Weaknesses-Opportunities) Strategies, 5 (five) ST (Strengths-Threats) Strategies and 5 ( five) WT (Weaknesses-Threats) Strategies. So based on the SWOT matrix table that can implement 20 strategy steps, there is a strategy that is a priority of the QSPM above on strengths and opportunities, namely by implementing the strategy "PT Bank Central Asia Tbk KCU Medan can increase the use of digital platforms such as mobile banking and other applications to facilitate customers". The selection of this strategy is carried out through an assessment of the attractiveness (Attractiveness Score) obtained from various alternative strategies produced in the SWOT analysis.